If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(17/2)*y = -17 // + 17
(17/2)*y+17 = 0
17/2*y+17 = 0 // - 17
17/2*y = -17 // : 17/2
y = -17/17/2
y = -2
y = -2
| 8+3(s-6t)= | | x^2y^4z/(x^2y)3*(x^10y^5z^4)^2/y^3z^2 | | 3(8+3/2y)+4y=7 | | 1/2(n+5)+1/3(n+3)=6 | | 5+2(x-3y)= | | -75=5(7n+6) | | 7t+18-4= | | -1x^2+12x-36=0 | | 2x^4-2x^3-11x^2+4x+8=0 | | 4(3x+7)-6(3x-5)=10x+3(2x-8) | | 4.9x^2+8x-30=0 | | .5(2m+6)=.25(8+8m) | | 3x^2-8x=9 | | 4.9x^2+8t-30=0 | | .25(2m-20)=.25(8-8m) | | (3x+7)(5x-1)= | | -35=5-2x+7x | | (2lb-5)-5(4b+4)=-3 | | 10-24d=4-5(2d+9)+3d | | 35-15x=-8x | | 7k+1=2k-1 | | 8w+w+6w= | | 35-15x=8x | | .5(-12m+6)=.25(-20+8m) | | (-8x-7)(-7x-3)= | | N+19=16 | | 6x^2+78x=-216 | | (8x+6)(8x^2+7x+8)= | | 8c*3e= | | -p-2p+3=-6 | | 6+x+-5+2x=x | | 29=2u+13 |